Heme oxygenase 1 (HMOX1) gene expression in hemodialysed uremic patients - Maróti, Zoltán (Acta Biologica Szegediensis, 2003)
The oxidative stress and the released heme molecule of degrading red blood cells during hemodialysis induce the expression of heme oxygenase 1 gene (HMOX1). The goal of our study was to measure the expression of HMOX1 during dialysis and compare it with the common oxidative markers. We established a cRT-PCR (competitive reverse transcriptase PCR) method to measure the mRNA levels. The mRNA levels were calculated to the white blood cell count respectively for each sample. We measured a 1-5-fold increase in the HMOX1 gene expression after the dialysis session, which dropped back to the original value 48 hours after the dialysis. The base level of HMOX1 mRNA of hemodialysed patients before dialysis was in the range of normal controls. The changes in mRNA levels showed significant correlation with the plasma hemoglobin (r=0.72, p<0.001) and plasma bilirubin (r=0.71, p<0.002) changes. We found no correlation between the changes of mRNA levels and other biochemical markers (GSH, GSSG). Our results suggest that the induced HMOX1 expression during hemodialysis is primarily due to the undergoing hemolysis.